Students’ Satisfaction of School Environment The Case of Four Elementary Schools in Shiraz City - Seyyed Mohammad Hossein Zakeri; Sedigheh Honarmand (صفه)
Post-Occupancy Evaluation (POE) is a useful method for studying design problems and improving future designs. This paper reports the results of a POE study conducted in four dilapidated and renovated elementary schools in Shiraz City. Students’ satisfaction of environmental properties such as lighting, sound, temperature, color, dimensions and materials is assessed. In case of properties such as thermal comfort, students’ satisfaction levels are compared with common international standards, as well. The study also includes measuring environmental parameters, as well as questioning students through questionnaires on thermal comfort. The responses were tested for demonstrating pair-wise and overall variance significance. The results include insights into actual user satisfaction factors. In particular, it turns out that student satisfaction of thermal comfort is less in renovated buildings despite the newer HVAC systems installed. It is further noted that thermal standards are not observed in the renovation design, in particular due to the priority attached to structural retrofitting in comparison with other design requirements such as provision of comfort conditions.